Comparative evaluation of the effects of consumption of colombian agraz (Vaccinium meridionale Swartz) on insulin resistance, antioxidant capacity, and markers of oxidation and inflammation, between men and women with metabolic syndrome (2020)
ABSTRACT: The metabolic syndrome (MS) is a constellation of related factors that increases the risk of developing cardiovascular diseases. Vaccinium meridionale Swartz contains polyphenols that could modulate some components of MS. Epidemiological and intervention studies have shown differences between men and women in MS components and antioxidant capacity. The objective of this study is to compare between men and women with MS the effects of agraz consumption on insulin resistance, antioxidant capacity, and markers of oxidation and inflammation. Men and women diagnosed with MS according to the Adult Treatment Panel III criteria were recruited in a double-blind, crossover study of 12 weeks. Participants were assigned to consume agraz nectar or placebo over 4 weeks. After 4 weeks of washout, they were switched to the alternative treatment. At the end of each period, the components of the MS, insulin resistance, antioxidant capacity, and some oxidative (oxidized low-density lipoprotein [oxLDL]; thiobarbituric acid reactive substances) and inflammatory (high-sensitive C-reactive protein [hs-CRP]) markers were evaluated. After consuming agraz, there was a tendency to increase the levels of antioxidants and to reduce the levels of hs-CRP in both genders. In addition, women who increased their serum phenols after consuming agraz had a significant reduction in insulin resistance, which was different from the results in men. Regarding men, those who increased their serum antioxidant capacity after consuming agraz had a better effect on the reduction of oxLDL levels that was significant compared to women. There are important differences between genders in the effects of agraz consumption in adults with MS.